Rebound hyperbilirubinemia in newborns more than 35 weeks of gestational age at tertiary care center: a descriptive study (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Rebound hyperbilirubinemia is defined as a total serum bilirubin (TSB) value sent following stopping of phototherapy that requires reinstitution of phototherapy. Identification of the risk factors for rebound hyperbilirubinemia facilitates early discharge of newborns without risk factors.Method: This was a hospital based prospective observational study conducted in a tertiary care centre of Nepal and included 71 newborns born ≥35 weeks of gestational age requiring phototherapy for neonatal jaundice between October 2019 to October 2020. Following complete examination, phototherapy was started and stopped on the basis of threshold graphs of National Institution for Health Care and Excellence (NICE). A rebound TSB was measured 12 hours after stopping phototherapy. A rebound TSB value requiring phototherapy was considered significant. Risk factors like sex, age at onset of jaundice, sepsis, blood group incompatibilities were studied. Data entry and analysis were done using Epi info 7 and Easy R software.Result: Out of total 71 cases, significant rebound hyperbiliubinemia was found in 15.49%. The cases with rebound had male predominace (81.81%), 54% developed jaundice before 72 hours of life, 28.5% had ABO setting and 21.40% had sepsis. The median difference in TSB value from threshold value at initiation and stoppage of phototherapy for rebound cases were 3.50 and 3.80 respectively.Conclusion: Rebound hyperbilirubinemia should be assessed in those babies with risk factors and other babies may be discharged without measuring rebound TSB and rather be called for early follow up.